Perilaku Birokrasi dalam Pelayanan Pajak Bumi dan Bangunan di Desa Tuladenggi Kecamatan Telaga Biru - Agreyz Fratiwi H. Kalay; Rustam Tohopi; Yacob Noho Nani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The background of this study is based on fluctuations in the realization of PBB in Tuladenggi Village, Telaga Biru Subdistrict, which has not consistently reached its target, even though PBB is an important source of support for local revenue. This condition is caused by low awareness and compliance among taxpayers, limited understanding among the community regarding payment mechanisms, and suboptimal bureaucratic behavior in providing services. The purpose of this study is to describe the behavior of the bureaucracy in PBB services in Tuladenggi Village, Telaga Biru District, with a focus on the aspects of responsibility, responsiveness, and commitment and consistency of village officials. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results show that bureaucratic behavior in PBB services in Tuladenggi Village is already in place, but it is not yet fully optimal. In terms of responsibility, officials have distributed SPPT and conducted socialization, but the information is often late and unclear. In terms of responsiveness, officials have attempted to adjust their approach to the community's conditions through direct services and personal communication, but some community members feel that some officials are still not proactive enough. In terms of commitment and consistency, village officials have demonstrated their seriousness through administrative record-keeping, routine evaluations, and proactive services, although they still face obstacles.